ANALISIS PENGARUH UPAH MINIMUM PROVINSI, RATA-RATA LAMA SEKOLAH DAN PERTUMBUHAN EKONOMI TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TIMUR - Danik Firdania; Niniek Imaningsih (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2026)
Employment absorption serves as one of the key indicators in assessing the success of economic development within a region. A high level of employment absorption reflects a healthy economic condition, in which economic growth is capable of creating broad and quality employment opportunities. East Jawa Province became the focus of this study, as it had the lowest percentage of workers employed in the formal sector among all provinces in Java Island in 2024, amounting to 38,51%. This condition illustrates that the labor market in East Java hasn’t yet functioned optimally in absorbing the labor force. The purpose of this study is to determine the effect of the Provincial Minimum Wage (PMW), Average Years of Schooling, and Economic Growth on Employment Absorption in East Java Province. The research employs a quantitative approach using multiple linear regression analysis as the analytical method. The results indicate that both the Provincial Minimum Wage (PMW) and Average Years of Schooling have a significant effect on employment absorption in East Java Province. Meanwhile, Economic Growth shows no significant effect on employment absorption.